Dynamics and Statics Analysis of Manipulator of Coalmine Detection Robot - Li Yang; Liu Sumei; Qu Dongdong; Shi Mingming (Jixie chuandong)
Aiming at the actual situation of coal mines unmanned area,a four wheels drives small space detecting robot system for collecting information and samples of the underground environment is designed and developed. The robot is composed of a robot mechanism,travel mechanism,the controller and manipulator mechanism. The robot system components are described,the dynamics and static analysis of the 5 degrees of freedom manipulator is conducted to verify the rationality of its structural design and bearing performance in practical work. The results show that the change of each robot joint torques stable and did not exceed the limits value of the motor to provide. The maximum deformation of forearm is 0. 012 397 mm,the maximum stress on the system configuration 15. 802 9 MPa is little affected,it shows that 5 DOF manipulator type selection is accurate,structure design is reasonable,the practical needs of the coal mine is met.